Measurement of circulating biliary antigen-antibody immune complex in the patients of primary biliary cirrhosis using ELISA - YAMAMOTO, Yasuro; OKINO, Minoru; OONISHI, Saburo; MIYAZAKI, Masako (Kanzo, 1986)
We purified the hepatic bile duct antigen from the human bile and confirmed that this antigen showed the antigenic cross reactivity with salivary gland duct, pancreatic duct and renal tubulus, but no cross reactivity with other organs. And we prepared the species specific antibody (bile duct antibody) against the bile antigen in rabbits to detect the bile antibody in circulating immune complex from the patients with PBC by using ELISA. In PBC, 20 of 68 cases showed positive results (29.4%). In contrast, bile antibody was detected in none of 3 cases with lupoid hepatitis, 1 of 4 SLE, 1 of 6 rheumatoid arthritis, 1 of 10 Sjogren's syndrome which is often associated with PBC, and 2 of 36 chronic pancreatitis. The present study showed that bile antibody was contained frequently within circulating immune complex from patients with PBC. These findings support that PBC is likely to be a autoimmune disease.